Pojok Baca dan Belajar Anak di RW 03 Kelurahan Kali Baru Jakarta Utara - Kenny Chandra Kusuma; Rosna Elfrina Sitompul; Hasan Kamil; Rafli Mulkan Mustaqim; Indrawati Indrawati (Lembaga Pengembangan Kinerja Dosen, 2025)
The Children’s Reading and Learning Corner program is a community service activity implemented by Group 7 of the Community Service Program (KKN) from Universitas 17 Agustus 1945 Jakarta in Kalibaru Subdistrict, North Jakarta. This program was designed to address the challenge of low reading interest and the limited access to learning facilities among children in the local community. The main target of the activity was children aged 5–8 years, with the objective of increasing reading interest, strengthening basic cognitive skills, and fostering positive learning habits from an early age. The program was carried out through interactive learning methods with a thematic approach, combined with group discussions, question-and-answer sessions, shared reading, and simple practices that encouraged active participation. The learning materials covered Basic Mathematics, Indonesian Language, and General Knowledge, all adjusted to the children’s comprehension levels. In addition, a coloring competition was held to foster creativity, train fine motor skills, and create a fun and engaging learning atmosphere. Evaluation results indicated a significant improvement in children’s enthusiasm for learning, better understanding of the provided materials, and more active involvement during the sessions. The children also demonstrated increased self-confidence, particularly when asked to read aloud or answer questions in front of their peers. Furthermore, the provision of a bookshelf in the community hall became a strategic step to establish a sustainable reading space that could be used outside of program hours. Overall, the program successfully achieved its intended goals and is considered feasible to be expanded to other areas. Additional support in the form of a wider collection of books, more creative learning media, and consistent community involvement will be key factors in ensuring the sustainability and long-term impact of the program.